Shocking frogs : Galvani, Volta, and the electric origins of neuroscience - Piccolino, Marco (Oxford University Press, 2013)
"Frogs, Torpedoes, and Sparks: Galvani, Volta, and Animal Electricity is an English translation of Rane, torpedini e scintille. Galvani, Volta e l'elettricità animale (Torino, Italy: Bollati-Boringhieri, 2003)"--